2022
DOI: 10.3390/diagnostics12020331
|View full text |Cite
|
Sign up to set email alerts
|

Anterior and Posterior Cruciate Ligaments Mechanoreceptors: A Review of Basic Science

Abstract: Proprioception is a specialized sensory modality encompassing the movement of the joint and its position in space, and it involves the conversion of mechanical deformation of tissues into neural signals. Mechanoreceptors are specialized nerve structures able to transmit mechanical deformation through electrical signals to dorsal root ganglion sensory neurons and are abundant in the muscles, tendons and ligaments of the knee joint. They are believed to play an important role in knee proprioception and dynamic k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Firstly, retention of the native ligament. This could be important given the variety of mechanoreceptors that have been identified in the PCL which aid knee stability [ 1 , 32 ]. A recent meta-analysis reported loss of proprioception in PCL deficient knees after PCL reconstruction [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, retention of the native ligament. This could be important given the variety of mechanoreceptors that have been identified in the PCL which aid knee stability [ 1 , 32 ]. A recent meta-analysis reported loss of proprioception in PCL deficient knees after PCL reconstruction [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PCL is one of the most important ligaments of the knee joint; it mainly plays a role in preventing the tibia from moving backward relative to the femur and providing knee joint dynamic stability through proprioception and muscle activity. 2 Proprioception includes perception of the static position, displacement, velocity, acceleration, and muscle force of body parts. 3 Proprioception depends on mechanoreceptors, which are distributed in many tissues of the knee joint.…”
Section: Discussionmentioning
confidence: 99%
“…However, Sha et al used immunohistochemical assays to show that there was no significant quantitative variation in the residual mechanoreceptors throughout the injury duration [ 37 ]. Another study showed that the mechanoreceptors existed in the cruciate ligaments, articular capsule, the lateral structures such as the lateral collateral ligament and the anterolateral ligament, tendons and muscles of the knee [ 8 ]. Trieb et al found that instead of normal ligament tissue 6 months after ACLR with LARS, there were only fibroblasts and some endothelial cells surrounding the ligament fibers [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proprioception is the synthesis of the sensory modality of joint movement, joint position, and tactile sense encompassing a joint, whether conscious or unconscious [ 7 ]. Proprioception has been defined as the afferent information arising from the internal peripheral area of the body and contributing to postural control, joint stability, and specific conscious sensations [ 8 ]. The ACL not only provides mechanical stabilization but also contributes to proprioceptive functions, by means of the various mechanoreceptors within its structure, and at the same time, the ACL can detect changes in tension, speed, acceleration, direction of movement, and the position of the knee joint [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%